Optimizing Students' Language Skills Through a Multimodal Learning Model in Indonesian Language Learning in Elementary Schools: A Systematic Literature Review - Budi Febriyanto Febriyanto; Dadang Sunendar; Bachrudin Musthafa; Yuliawati Yuliawati; Agus Rofi'i (Jurnal Pendidikan Terapan, 2026)
Background: Multimodal learning has gained increasing attention in language education because it enables learners to construct meaning through text, visuals, audio, gesture, space, and social interaction. However, the literature remains fragmented, and no integrated model has been clearly established for Indonesian language learning in elementary schools. Purpose: This study analyses the conceptual and pedagogical characteristics and design components of multimodal learning, its influence on students' language-skill development, and the conceptual, methodological, and assessment gaps in the literature. Methods: This study used a Systematic Literature Review (SLR) design. Articles indexed in Scopus were selected through the PRISMA flow. The search identified 277 records, and 44 reports were included in the final analysis. Findings: The integration of text, visuals, audio, gestures, social interaction, and meaning-making activities within structured instructional designs characterises multimodal learning. Across the reviewed studies, it tends to support reading, writing, speaking, listening, vocabulary development, and communicative competence. However, its effectiveness varies depending on instructional design, teacher readiness, student characteristics, and classroom context. The literature also remains conceptually, methodologically, and contextually fragmented, especially regarding Indonesian language learning in elementary schools. Research implications: The findings provide a conceptual foundation for developing Indonesian language instruction that is more contextual, participatory, and supportive of integrated language-skill development. They also offer guidance for designing more coherent instructional models, implementation strategies, and assessment systems for elementary school settings. Conclusion: Multimodal learning should be understood not merely as media variation, but as a design of meaning and learning experience. Future research needs to test integrated multimodal models directly in Indonesian elementary school language classrooms. Originality: This study systematically maps the conceptual foundations, pedagogical patterns, empirical trends, and research gaps in multimodal learning as a basis for developing Indonesian language-learning models in elementary schools. The review highlights that the existing literature remains fragmented and has yet to produce many fully integrated models for this context.